Organogenesis in-vitro using three tissues types of tree tomato [Solanum betaceum (Cav.)] - Murillo-Gómez, Paola Andrea; Hoyos S, Rodrigo; Chavarriaga Aguirre, Paul (Universidad Nacional de Colombia, 2017)
Tree tomato is a fruit with great economic potential due to its high nutritional value. The induction of direct organogenesis in this species is a great alternative for clonal propagation of disease-free plants, and also useful for genetic transformation. In this study was assessed the induction of organogenesis in vitro using three different tissues: leaves, petioles and sexual seeds of the variety Common. All tissues were cultured on MS supplemented with agar, sucrose and TDZ or BAP phytohormones at 0.5 to 3 mg L-1, combined or not with the auxins IAA and NAA. Although petioles and seeds had a great potential for regeneration of plantlets, leaves produced more shoots (average of 18.4 shoots/explant) on medium containing TDZ 0.5 mg L-1. Additionally, its easy handling and resistance to physical damage may be useful traits to perform genetic transformation. The highest average of shoots produced from seeds and petioles were 4.3 and 3.1 shoots/explant, respectively. The production of multiple shoots in petioles was influenced by low concentrations of auxins. The emergence of the radicle in the seeds was important for the formation of shoots.